2021
DOI: 10.1016/j.jsams.2020.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Temperature regulation during exercise in the heat: Insights for the aging athlete

Abstract: Objective: The purpose of this review is to evaluate the currently-available literature regarding the impact of both primary aging and age-related fitness on thermoregulatory function during exercise in the heat. In so doing, we aim to (1) characterize the influence of fitness in mitigating age-related declines in thermoregulation, (2) address the limitations of prior experimental approaches for investigating agerelated thermoregulatory impairments, (3) examine to what extent aerobic fitness can be maintained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…With age, impaired secretion of sweat glands along with reduced vasodilation of dermal arterioles and the loss of subcutaneous fat led to thermoregulation disorders (Ding et al, 2021b;Lazarus et al, 2019). Repair processes of collagen remodeling, cell proliferation, and wound metabolism in the elderly were shown to be delayed (Kenney et al, 2021;Mistry et al, 2021). Furthermore, a more pronounced inflammatory phenotype has been uncovered in aged skin wounds, featured by the persistence of neutrophils and a higher abundance of inflammatory macrophage subsets compared to younger counterparts (Kenney et al, 2021;Vu et al, 2022).…”
Section: Physiological Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…With age, impaired secretion of sweat glands along with reduced vasodilation of dermal arterioles and the loss of subcutaneous fat led to thermoregulation disorders (Ding et al, 2021b;Lazarus et al, 2019). Repair processes of collagen remodeling, cell proliferation, and wound metabolism in the elderly were shown to be delayed (Kenney et al, 2021;Mistry et al, 2021). Furthermore, a more pronounced inflammatory phenotype has been uncovered in aged skin wounds, featured by the persistence of neutrophils and a higher abundance of inflammatory macrophage subsets compared to younger counterparts (Kenney et al, 2021;Vu et al, 2022).…”
Section: Physiological Characteristicsmentioning
confidence: 99%
“…Repair processes of collagen remodeling, cell proliferation, and wound metabolism in the elderly were shown to be delayed (Kenney et al, 2021;Mistry et al, 2021). Furthermore, a more pronounced inflammatory phenotype has been uncovered in aged skin wounds, featured by the persistence of neutrophils and a higher abundance of inflammatory macrophage subsets compared to younger counterparts (Kenney et al, 2021;Vu et al, 2022). Recent studies have also revealed an increase in immuno-suppressive activity in the aging process of the skin (Salminen, 2020;Salminen et al, 2022).…”
Section: Physiological Characteristicsmentioning
confidence: 99%
“…Progressive impairments in the human sweating response occur naturally with aging owing to reduced peripheral sensitivity to acetylcholine, the neurotransmitter predominantly responsible for eccrine sweating, and atrophy of the sweat glands. 93 Above the age of 60 y, thermoregulatory sweating can decline by up to 25%, although these impairments can be delayed by regular aerobic training. 94 Anticholinergic medications, such as many antidepressants and psychotropic medicines, also theoretically attenuate sweating, 95 as do other medications that alter peripheral vasodilation, such as anti-adrenergics and beta-blockers.…”
Section: Possible Physiological Reasons For Epidemiological Resultsmentioning
confidence: 99%
“…Humidity has been suggested as a factor of heat dissipation, and consequently, an increase of humidity would affect negatively the balance between heat production ad dissipation ( Bouscaren et al, 2019 ). In addition, the thermoregulation has been well-documented to be impaired with aging reducing sport performance for master athletes especially in hot environmental conditions ( Kenney et al, 2020 ). These age-related differences in thermoregulation might be attributed to differences in performance related characteristics (e.g., physical fitness and body composition) ( Kenney and Munce, 2003 ).…”
Section: Discussionmentioning
confidence: 99%